2017
DOI: 10.1002/eap.1435
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the loss of large, energy‐dense prey: a potential bottleneck for Weddell Seals in the Ross Sea

Abstract: Abstract. Extraction of Antarctic toothfish (Dissostichus mawsoni) in the Ross Sea began in 1997, following a management plan that targets the largest fish with a goal of reducing the spawning biomass by 50% over 35 yr. We investigate the potential long-term consequences of the reduced availability of this prey for Weddell seals (Leptonychotes weddellii). Energy demands in seals are acute, especially immediately following lactation, when females must recover substantial mass and cope with molting costs. We tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 78 publications
(121 reference statements)
1
25
0
Order By: Relevance
“…Large among‐individual heterogeneity in prey consumption has been documented in Weddell seals (Goetz ), and recent work has suggested that breeding probabilities may be sensitive to the consumption of Antarctic toothfish ( Dissostichus mawsoni ), an energy‐dense prey item (Salas et al. ), such that individuals who consume more toothfish are more able to meet the demands of reproduction and lactation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large among‐individual heterogeneity in prey consumption has been documented in Weddell seals (Goetz ), and recent work has suggested that breeding probabilities may be sensitive to the consumption of Antarctic toothfish ( Dissostichus mawsoni ), an energy‐dense prey item (Salas et al. ), such that individuals who consume more toothfish are more able to meet the demands of reproduction and lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Such residual variation among individuals may reflect underlying among-individual differences in physiological, or metabolic functions (Wheatley et al 2008a, b), in addition to differences in resource acquisition. Large amongindividual heterogeneity in prey consumption has been documented in Weddell seals (Goetz 2015), and recent work has suggested that breeding probabilities may be sensitive to the consumption of Antarctic toothfish (Dissostichus mawsoni), an energy-dense prey item (Salas et al 2017), such that individuals who consume more toothfish are more able to meet the demands of reproduction and lactation.…”
mentioning
confidence: 99%
“…There are plenty of benthic fish species, of lower energy density (Lenky et al 2012), but these would be far easier to deplete by a persistently located group of seals (Testa et al 1985, Buckley 2013. Increased foraging time leads to energy loss, which needs to be replenished, especially for females who are regaining the 40% of body mass lost during pup rearing (Salas et al 2017). The effect of distance to deep water was greatest in the ERS.…”
Section: Factors Affecting Seal Haul-out Presencementioning
confidence: 99%
“…Because Weddell seals are dark and large (400− 600 kg, 1.5 × 3−4 m), very high-resolution (VHR) satellite imagery has been used to quantify their distribution and numbers even in the most remote sections of the Antarctic coast (LaRue et al 2011, Ainley et al 2015a. Given that the diet of Weddell seals depends on the commercially important Antarctic toothfish (Ponganis & Stockard 2007, Ainley & Siniff 2009, Salas et al 2017) and silverfish (one of the principal forage fish in coastal Antarctic waters; La Mesa & Eastman 2012), the ability to assess population size and distribution of Weddell seals at regional scales may render the species a reliable indicator of ocean health, and thus a target of the Convention for the Conservation of Antarctic Marine Living Resources (CCAMLR) Ecosystem Monitoring Program (CEMP; www.ccamlr.org) and/or the incipient Research and Monitoring Program for the Ross Sea Region Marine Protected Area (Dunn et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported little annual variation in survival rates for adult female Weddell seals across years that encompassed diverse environmental conditions, including a major iceberg event that led to a decrease in primary productivity (Arrigo, van Dijken, Ainley, Fahnestock, & Thorsten, ; Chambert, Rotella, & Garrott, ; Rotella, Link, Chambert, Stauffer, & Garrott, ). Female Weddell seals seem to breed each year but exhibit delayed implantation of the fertilized egg 1–2 months after breeding (Lake, Burton, Barker, & Hindell, ; Salas et al, ), and implantation seems to not occur during years with challenging environmental conditions (Chambert et al, ). This strategy would enable the females to avoid excessive energy expenditure associated with reproduction (i.e., gestation and lactation) and avoid augmented survival risks.…”
Section: Introductionmentioning
confidence: 99%